Hot shortness mechanism and heat treatment of Cu containing carbon steel - Yeşiltepe, Selçuk; Şeşen, Mustafa Kelami (İdris Karagöz, 2021)
Hot shortness mechanism in low carbon steels is studied with 1.0% wt. Cu containing steel. Slabs were prepared with scrap rebar steel and Cu billets. Slab was smelted in induction furnace and casted in mould. Casted sample was investigated with optical microscopy and chemical analysis was done with optical emission spectroscopy. Slab was heated up to 1200 oC and annealed for 1 hour before the hot rolling process. Hot rolling process was carried out with hot rolling press capacity of 25 tonnes for height reduction of 60%. Hot rolled slab was investigated with optical microscopy and scanning electron microscopy (SEM) techniques to observe the segregation of Cu. Hot rolled samples were heat treated at 800 oC, 900 oC and 1000 oC for 1 and 4 hours. Samples were cooled at air and water quenched. All samples were observed with optical microscopy and selected samples were examined with SEM. Cu segregation did not occur in as-cast condition but after hot rolling process Cu segregation occurred. Heat treatment decreased the segregation degree of Cu yet Cu particles were observed in microstructures.
Keywords: Material Production Technologies; Malzeme Üretim Teknolojileri